Meningkatkan Hasil Belajar Kebugaran Melalui Penerapan Ice Breaking Siswa SDN 29 Songka - Sry Agustina; Ahmad, Ahmad; Kahar, Irsan; Hidayat, Rachmat; Riswanto, A Heri; Hamzah, Fajri (Universitas Hamzanwadi, 2025)
Low student interest and learning outcomes in physical fitness classes at SDN 29 Songka were the background for this study. The main problems included a monotonous learning atmosphere, lack of active participation, and student motivation, as evidenced by only 44% of students achieving the minimum passing grade (KKM) at the beginning of the study. This study aims to improve students' physical fitness learning outcomes through the application of ice breaking techniques. This study uses the Classroom Action Research (CAR) method, which is carried out in two cycles. Each cycle consists of the planning, action, observation, and reflection stages. The research subjects were 25 fifth-grade students. Data were collected through observation, tests, and documentation, then analyzed quantitatively and qualitatively. The results showed a significant increase in learning outcomes in the cognitive, psychomotor, and affective domains. Classical mastery of knowledge increased from 48% (Cycle I) to 84% (Cycle II). In the skill domain, mastery increased from 60% to 96%, and in the attitude domain from 72% to 100%. The application of ice breaking successfully created a pleasant learning atmosphere and increased student activity. It was concluded that the application of ice breaking was effective in improving learning outcomes and student interest in physical fitness learning.